A Post Occupancy Quality Evaluation Model for Preschool Settings’ Interior Spaces - Izadpanah, Shirin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The overall purpose of current thesis is to contribute a knowledge based on interpretation of transactional relationship between the design of educational spaces and patterns of everyday learning experiences. Based on the findings on the lack of evaluation models that controls the design quality of educational spaces against the requirements of learning experiences, this thesis establish a systematic path for shaping the design evaluation models that would concern the learning environment within interiors. With the growth of preschool education as compulsory education and increase in number of preschool settings, the researches focus on shaping a model for interior space of preschools. The research is built upon accomplished researches and studies in field of education, design, architecture and environmental studies and reviews are conducted by using theme analysis, structured review and taxonomy analysis. This study includes three main stages of research: identifying the indicators of ‘Quality without a Name’ in preschool spaces, Definition of design quality in preschool spaces and Model proposal. In first phase the aim was identifying the requirement of evaluating the concept of ‘Quality without a Name’ in preschool spaces. Findings in this phase illustrate the subjects design of preschool spaces need to enhance their requirements. According to the findings educational program, children’s learning and development, teachers’ performance and parents’ participation were defined as the indicators of ‘Quality without a Name’ and developmental based and holistic learning experiences were defined as communal path of learning experiences that keep happening in preschool settings. In second phase of the research design and arrangement of preschool spaces is interpreted in relation to the requirements of identified indicators of ‘Quality without a Name’ during communal path of learning experiences. The theory that is established based on this interpretation shaped the theoretical background of the model. In final phase of the research the established theory in previous phase were classified into evaluation subsets and these subsets shaped the structure of the model. To accomplish this phase, the necessary evaluation techniques were identified for the identified subsets and final framework of the model were established. The systematic path of shaping the model that is presented in this thesis may serve as a starting point for shaping post occupancy design evaluation models that would consider the requirements of learning environment in evaluating the design quality for educational facilities and improve the theoretical knowledge in this field accordingly. The conclusion suggests adoption of the model on variety of preschool cases to develop and improve the evaluation framework of the model instantly. A theoretical framework of current thesis shapes an interdisciplinary knowledge by connecting the field of interior design and education. This theoretical bridge would benefit both designers and educationalists to use the evaluation model and increase their awareness on consequences of the contrary discipline. Keywords: Preschool Settings, Educational Spaces Quality, Early Childhood Environment Design and Arrangement, Children’s learning process, Everyday Learning Experience

ÖZ: Bu tez çalışmasının temel amacı, bütünlüklü bir yaklaşımla eğitim mekanları tasarımını, günlük yaşamın deneyimlendiği örüntülere bağlı olarak yorumlamak ve değerlendirmekle bir bilgi donanımı kurgulamaktır. Yapılan çalışmalar sonucunda, eğitim mekanlarının tasarım kalitesini, günlük yaşamın gereksinmelerine göre değerlendirmekte olan bir yaklaşım (model) bulunmadığından bu tez çalışmasında, sözü edilen değerlendirmeler ışığında iç mekandaki yaşam örgütlenmesi de dikkate alınarak sistematik bir yaklaşımla değerlendirme modeli oluşturulmuştur. Okul öncesi eğitim, zorunlu eğitimin bir parçası olarak kabul edilmekte olduğundan, söz konusu eğitim yapıları artış göstermiş ve bu alanda doğan ihtiyaçlar neticesinde, okul öncesi eğitim mekanları için ‘değerlendirme modeli’ kurgulanmıştır. Eğitim, tasarım, mimarlık ve yapısal çevre çalışmalarına göre kurgulanmış ve hazırlanmış olan bu tez, asal düşünce (tema) analiz (theme analysis), yapılandırma amacı ile literatür taraması (structured review) and taksonomi analizi (taxonomy analysis) yaklaşımları ile metodoloji (yöntembilim) kurgulanmıştır. Yapılan çalışmalar ışığında tez üç ana aşama içermektedir. Bu aşamalarda, okul öncesi mekanlarda ‘Quality without a Name’ / ‘İsmlendirilemez Kalite’yi tanımlayan göstergeçler belirlenmiş; okul öncesi mekanlarda gerekli olan tasarım kalitesi tanımlanmış ve önerilen model oluşturulmuştur. Birinci aşamadaki araştırma amacı, ‘İsmlendirilemez Kalite’nin göstergeçleri, okul öncesi mekanlar için gereksinimleri tanımlamak olmuştur. Bu aşamadaki bulgular, iç mekan tasarımı ile ilgili konuları tanımlamıştır. Bu bulgular ışığında eğitim, çocukların gelişimi - öğrenimi, öğretmenlerin performansı ve ebeveyin katılımı konuları ‘İsmlendirilemez Kalite’nin göstergeçleri olarak tanımlanmış, aynı zamanda ‘çocuk gelişimine dayalı deneyimler’ ve ‘bütüncül deneyimler’ okul öncesi mekanlarda devamlı yapılan eğitim deneyimleri olarak ortaya konmuştur. İkinci aşamada, okul öncesi eğitim yapılarının iç mekan tasarımı, ‘İsmlendirilemez Kalite’nin göstergeçleri göz önünde bulundurularak tartışılmıştır. Bu aşamada oluşturulan kurgu, önerilen modelin teorik alt yapısını oluşturmuştur. Son aşama olan üçüncü kısımda ise, bir önceki aşamada oluşturulmuş olan teori yardımı ile alt dallar kurgulanmış ve modelin değerlendirme stürüktürü yapılandırılmıştır. Daha sonra ise, her değerlendirme maddesi için kullanılması gereken değerlendirme teknikleri oluşturulmuş ve modelin son çerçevesi şekillendirilmiştir. Modelin şekillendirilmesi için oluşturulan söz konusu sistematik yaklaşım, okul öncesi eğitim yapılarının iç mekan tasarımlarının yanı sıra, farklı eğitim yapıları için tasarım değerlendirme modeli oluşturulması amacı ile de kullanılıp, değerlendirme modeli ile elde edilen bulgular yeni teorilere ışık tutabilme olanağı sağlamaktadır. Çalışmanın sonucunda oluşturulan model kullanılarak, farklı okul öncesi eğitim yapılarının iç mekan tasarımına ait değerlendirmeler de yapılıp modelin dinamik özelliğe sahip yapısı ile devinimi sağlanarak yenilenebilir. Bu tezde oluşturulmuş teorik kurgu, iç mekan tasarım alanı ile okul öncesi eğitimi buluşturarak disiplinler arası bilgi birikimi ve birlikteliği sistematik bir şekilde ortaya koymaktadır. Oluşturulan disiplinler arası söz konusu teorik kurgu,disiplinler arası farkındalığın oluşmasında tasarımcılara ve eğitimcilere katkı sağlamakta, aynı zamanda modeli kullanmak için de yardımcı olmaktadır. Anahtar Kelimeler: Okulöncesi Binalar, Eğitim Mekanların Kalitesi, Çocuk Alanraın Çevre Tasarımı ve Düzenlemesi, Çocukların Öğrenme Süreci, Günlük Eğitim Deneyimleri.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Assoc. Prof. Dr. Kağan Günçe.
Keywords: Architecture; Educational Spaces-Schools-Design and Architecture; Preschool Settings; Educational Spaces Quality; Early Childhood Environment Design and Arrangement; Children’s learning process; Everyday Learning Experience